Characterization of Gambierdiscus lapillus sp. nov. (Gonyaulacales, Dinophyceae): a new toxic dinoflagellate from the Great Barrier Reef (Australia). Issue 2 (30th January 2017) - Kretzschmar, Anna Liza; Verma, Arjun; Harwood, Tim; Hoppenrath, Mona; Murray, Shauna
Abstract : Gambierdiscus is a genus of benthic dinoflagellates found worldwide. Some species produce neurotoxins (maitotoxins and ciguatoxins) that bioaccumulate and cause ciguatera fish poisoning (CFP), a potentially fatal food‐borne illness that is common worldwide in tropical regions. The investigation of toxigenic species of Gambierdiscus in CFP endemic regions in Australia is necessary as a first step to determine which species of Gambierdiscus are related to CFP cases occurring in this region. In this study, we characterized five strains of Gambierdiscus collected from Heron Island, Australia, a region in which ciguatera is endemic. Clonal cultures were assessed using (i) light microscopy; (ii) scanning electron microscopy; (iii) DNA sequencing based on the nuclear encoded ribosomal 18S and D8‐D10 28S regions; (iv) toxicity via mouse bioassay; and (v) toxin profile as determined by Liquid Chromatography‐Mass Spectrometry. Both the morphological and phylogenetic data indicated that these strains represent a new species of Gambierdiscus, G. lapillus sp. nov. (plate formula Po, 3′, 0a, 7″, 6c, 7‐8s, 5‴, 0p, 2″″ and distinctive by size and hatchet‐shaped 2′ plate). Culture extracts were found to be toxic using the mouse bioassay. Using chemical analysis, it was determined that they did not contain maitotoxin (MTX1) or known algal‐derived ciguatoxin analogs (CTX3B, 3C, CTX4A, 4B), but that they contained putative MTX3, and likely other unknown compounds.